2005
DOI: 10.1002/jcc.20225
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between adsorption energies of methyl on metals and the metallic electronic properties: A first‐principles DFT study

Abstract: A theoretical study of CH3 adsorbed on the (111) surface of some transition and noble metal surfaces M (M = Cu, Ni, Rh, Pt, Pd, Ag, Au) and on the Fe(100) is presented. We find that the hollow site is preferred more than the top one for Fe, Ni, Rh, and Cu, but it is the other way for Pt, Pd, Au, and Ag. In addition, a good linear relationship was observed between the chemisorption energy and d-band center for Group VIII metals or the square of the coupling matrix element for Group IB metals at the hollow site.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
24
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 54 publications
7
24
2
Order By: Relevance
“…The trend of our adsorption energy successfully satisfies the above linear relationship (Figure 4) for the chemisorption systems of HCOO adsorbed on these 9 metal surfaces, just as previous studies on CH 3 O as well as CH 3 adsorbed on the same metal surface site [9,10] . Moreover, we also found a similar formula of adsorption energy (Q) with ε d and 2 ad V as two parameters as follows:…”
Section: The Relationship Between Formate Adsorption Energy and D-bansupporting
confidence: 72%
See 4 more Smart Citations
“…The trend of our adsorption energy successfully satisfies the above linear relationship (Figure 4) for the chemisorption systems of HCOO adsorbed on these 9 metal surfaces, just as previous studies on CH 3 O as well as CH 3 adsorbed on the same metal surface site [9,10] . Moreover, we also found a similar formula of adsorption energy (Q) with ε d and 2 ad V as two parameters as follows:…”
Section: The Relationship Between Formate Adsorption Energy and D-bansupporting
confidence: 72%
“…Both ε d and 2 ad V reflect the properties of metal d-band, but we must determine which effect is the dominant factor for a given metal, because their effect is different: ε d will be attractive and 2 ad V will be repulsive. According to previous model [7,9,10] , it showed that the closer the d-band center to the Fermi level, the higher the adsorption energy. On the contrary, the larger the 2 ad V , the stronger the overlap, and the larger the repulsion, then inducing a smaller adsorption energy.…”
Section: The Relationship Between Formate Adsorption Energy and D-banmentioning
confidence: 94%
See 3 more Smart Citations